2015
DOI: 10.1140/epjd/e2015-50908-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the secondary electron yield from carbon nanoparticles and pure water medium

Abstract: The production of secondary electrons generated by carbon nanoparticles and pure water medium irradiated by fast protons is studied by means of model approaches and Monte Carlo simulations. It is demonstrated that due to a prominent collective response to an external field, the nanoparticles embedded in the medium enhance the yield of low-energy electrons. The maximal enhancement is observed for electrons in the energy range where plasmons, which are excited in the nanoparticles, play the dominant role. Electr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…It was suggested that the GDPR has a profound influence on the energy loss of the projectile. However, most of these studies were focused on measuring the GDPR contribution on the recoil-ion yields, whereas the electronspectroscopy-based measurements using a free C 60 molecule as the target are rather limited [9,[34][35][36][37]. This lack of experimental investigations on electron spectroscopy of C 60 can be, in part, attributed to the difficulties in detecting low-energy electrons.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the GDPR has a profound influence on the energy loss of the projectile. However, most of these studies were focused on measuring the GDPR contribution on the recoil-ion yields, whereas the electronspectroscopy-based measurements using a free C 60 molecule as the target are rather limited [9,[34][35][36][37]. This lack of experimental investigations on electron spectroscopy of C 60 can be, in part, attributed to the difficulties in detecting low-energy electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies of ionization of biomolecules with protons are reported by Paredes et al [24]. Finally, a theoretical analysis of secondary electron production in liquid water sensitized with carbon nanoparticles is reprorted by Verkhovtsev et al [9]. These works follow the previous volume's papers [25][26][27] and others.…”
Section: Introductionmentioning
confidence: 85%
“…On the scale of electromagnetic interactions, the effect of the presence of biomolecules in the medium on ionization cross sections, stopping power, dose deposition in a cell was explored [6,7]. Another advance on this scale was the analysis of secondary electron production by nanoparticles [8,9]. The radial dose deposition as well as transport of secondary particles on the scales pertinent to this transport have also been investigated [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…2015c). Due to the fact that the plasmon resonance energy for carbon NPs occurs at higher energies than for NPs of noble metals, it was proposed that NPs made of a combination of materials with different plasmon resonance energies will be able to exploit a larger spectrum of ion energies, leading to a more efficient electron production from such NPs.…”
Section: Radiotherapy With Gold Nanoparticlesmentioning
confidence: 99%